Art Museums and Galleries: Retrospective Repertoire of Imaginative Freedom (Proceeding of the International Conference on Arts and Humanities, 2021)
Art Museums and Galleries are wealth of imaginative freedom of the artists. The museums and galleries hold the mantle to repertoire traditional art for contemporary generations. While the artefacts displayed are product of freedom of dreams and beliefs, they were merely developed as a result of literary imagination. Museums and galleries facilitate the visitors by visual narratives of retrospective freedom and imagination; but are they effective in connecting the dots of history, imagination & freedom with culture? This research question is articulated by case studies of Maharaja Sawai Man Singh II Museum and Indian Contemporary Art (ICA) Gallery at Jaipur, in Rajasthan state of India. For museums and galleries exhibit paintings, the purpose of the study is to identify how they fuel the imagination of visitors by the means of traditional & cultural knowledge. This study conducts qualitative analysis amongst visitors at these two artistic venues to gather their perspectives of whether their visit justified completion of wheel of imaginative freedom from artists to visitors. The findings of the study revealed a significant role of museums and galleries in giving birth to imagination and gathering evidence of relativism.
Keywords: Museums; Art Galleries; Paintings; Imagination; Culture; Freedom